SURVEY AND CROSS-CULTURAL COMPARISON OF WATER SYMBOLISM IN THE ANCIENT BABYLONIAN AND EGYPTIAN COSMOLOGICAL CYCLES - Belot, Margot (School of Languages, Literatures and Curtural Studies. Discipline of Near and middle Eastern Studies, 2018)
This thesis focuses primarily upon obtaining a greater understanding of Babylonian and Egyptian mythical environments, through the use of water symbolism within the physical and mythological frames of their cosmological cycles. In the Babylonian and Egyptian cosmological corpora, water appears to be a symbolic natural element, omnipresent and essential in the establishment of the tripartite world. The objective of this study is then to attempt to gather and analyse a concise survey of sources on both Babylonian and Egyptian water symbolism within their creation corpora, and also to identify the role it held in their cosmographical cycles. Furthermore, this survey will aim to reflect in these myths and artefacts the common cultural and natural patterns, as well as knowledge of water symbolism present in Babylonian and Egyptian social and natural environments. Thus, showing the common parameters of water symbolism and cosmographical structures in Babylonia and Egypt as the result of an analogous response to similar environments, remains the principal concern throughout. Chapter One begins with an in-depth analysis and survey of water symbolism in the Babylonian cosmological cycle. It examines and categorises the numerous textual and pictorial sources of Babylonian water symbolism under three main sections: water as Creation, water as life and water as death. The purpose of this chapter is to highlight the plurality of water as a hierophany and as a complimentary dualistic element within the tripartite world. In Chapter Two, a thorough survey and study of water symbolism in the Egyptian cosmological cycle is conducted. Similarly to Chapter One, Chapter Two aims to identify and categorise the sources of Egyptian water symbolism under same three main topics: water as Creation, water as life and water as death. In this chapter, the environmental and mythological aspects of water as a hierophany are emphasised as being part of a larger concept: the tripartite world. Chapter Three seeks to compare and contrast the elements discussed in Chapters One and Two, by highlighting their common aqueous features. Additionally in this chapter, the social aspect of water symbolism through ceremonial and cosmographical features is investigated, for example the Babylonian and Egyptian New-Years’ festivals, which are shown as linked to the mythological and environmental aspects of water displayed in the previous two chapters. Hence, this thesis sheds light on a greater understanding of the context of use of water symbolism in Babylonian and Egyptian corpora. It seeks as well, to demonstrate the deficiency of ideas on water symbolism found in the meagre and sporadic references of scholarly research by highlighting the interconnectedness with water entrenched in the Babylonian and Egyptian civilisations. This shared conception of water is present within the cores of both civilisations.
Keywords: Egyptian civilisation